Bibliometric Analysis of Cost and Time Management In Handling Avalanches on National Roads In Mountainous Areas Using BIM - Ridho Alfarizi, Muhammad; Irfan Rifai, Andri; Indrastuti, Indrastuti; Prasetijo, Joewono (Pelopor Publikasi Akademika, 2024)
landslides on national roads in Indonesia's mountainous regions using BIM is a construction technology innovation that can help stakeholders to collaborate, visualize, and manage construction work well. The purpose of the study is to organize the literature and provide valuable insights into the research. The method used in the study was bibliometric analysis using the help of the Publish or perish application as a RIS and CSV metada withdrawal application, as well as the Vosviewer application. From the results of the analysis using the bibliometric method, there are 3 clusters of keywords and 26 keywords. In the development of the research year, the peak of research occurred in 2022, with the most dominant keyword BIM. The type of publication is dominated by journals by 33.7% and the most found publisher place is IEEE at 125. Based on the results of the analysis as a whole, America is the most dominant country and continent discussing research topics related to research topics.